2001
DOI: 10.5014/ajot.55.6.641
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Occupational Therapist Recommendations for Home Modifications for Falls Prevention

Abstract: A major barrier to adherence to home modification recommendations is that many older people do not believe that home modifications can reduce their risk of falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 12 publications
11
76
1
4
Order By: Relevance
“…6 In interventions with longer duration, adherence tends to decline. [34][35][36][37] Adherence rates for the group and home exercises of the current intervention were moderate. Adherence rates for the psychosocial group activities and lectures were lower than for the physical exercise groups.…”
Section: Discussionmentioning
confidence: 91%
“…6 In interventions with longer duration, adherence tends to decline. [34][35][36][37] Adherence rates for the group and home exercises of the current intervention were moderate. Adherence rates for the psychosocial group activities and lectures were lower than for the physical exercise groups.…”
Section: Discussionmentioning
confidence: 91%
“…stroke. These main factors, according to the literature, have included: a) lack of motivation to continue [10]; b) low confidence in the programme [6]; and c) the nature of the exercise programme, or the way in which these exercises are presented to the user [18]. In particular, the repetitive movements involved in rehabilitation exercises (over a period of time) could potentially result in a reduced interest in the programme [25].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Home modifi cation, involving the removal of hazards and the incorporation of safety features in the home, can also reduce falls when properly implemented. 23,24 Hughes et al 25 demonstrated that many elderly people advocated fall prevention strategies for their peers; however, they did not think that they themselves needed it. Furthermore, not many elderly people are aware of programmes available to them.…”
Section: Fallsmentioning
confidence: 96%